Designing Medume Media on Data Centering Materials Using Design Thinking Method - Riri Andini; I Luh Restini; Rita Lefrida (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
A teacher must be creative to get the attention of Generation Z students (“Gen Z”) in the learning process. One of the things that can be implemented is using media that suits the needs of student participants. In this study, the media designed is medume media and applied to data centering material.The purpose of the research is to design learning media that focuses on students' needs. The process of designing this media uses the Design Thinking method. The research sample consisted of four students from grade 8 junior high school. The sample selection was based on extreme left and extreme right criteria. This method starts from the stages of emphatize, define, ideate, and prototype. Then, it concludes with the testing stage. This research was conducted at SMP Negeri 4 Palu. It included qualitative approach. The researchers created an interactive media medume board. After the medume board was formed, it was applied in a classroom which discussed the said material. The result is that students were very enthusiastic and could understand the data concentration material quickly. In addition, the concept of data concentration becomes more concrete and easier to understand. This is because students can see the media used and interact directly with the data presented.